Community Participation towards the Development of the Community as an Agricultural Tourist Attraction at Ban Sawang Community, Lopburi Province - โยสุใจ , สุภารัตน์ (Academic and Research Journal of Liberal Arts (Online), 2022)
The study on community participation towards the development of the community as an agricultural tourist attraction at Ban Sawang community, Lopburi. The objectives were 1. to study the opinion level of the readiness potential in the community towards the development of the community as an agricultural tourist attraction, 2. to study the opinion level of the participation of people in the community towards the development of the community as an agricultural tourism attraction. This is quantitative research. The population consisted of people living in Sawang community, Khok Tum sub-district, Muang district, Lopburi. The sample consisted of 315 people. The results of the study revealed that the readiness potential of the community in terms of both the potential of the people in the community and the potential of the area in the community was at the highest level. When sorted by mean, it was found that the readiness potential of the area was greater than the readiness potential of the people in the community. As for the readiness potential of the area, the item with the highest opinion level was the easily accessible community with convenient transportation routes. As for the readiness potential of the people in the community, the item with the highest opinion level was agricultural skills and achievements of the people in the community as the cost of development towards becoming an agricultural tourist attraction. As for the participation of the people in the community towards the development of the community as an agricultural tourist attraction, the item that people in the community felt most strongly about and was the most important issue was the attitude, knowledge, and understanding towards participation.